1979
DOI: 10.1128/jvi.30.3.821-827.1979
|View full text |Cite
|
Sign up to set email alerts
|

Nature and distribution of feline sarcoma virus nucleotide sequences

Abstract: The genomes of three independent isolates of feline sarcoma virus (FeSV) were compared by molecular hybridization techniques. Using complementary DNAs prepared from two strains, SM-and ST-FeSV, common complementary DNAs were selected by sequential hybridization to FeSV and feline leukemia virus RNAs. These DNAs were shown to be highly related among the three independent sarcoma virus isolates. FeSV-specific complementary DNAs were prepared by selection for hybridization by the homologous FeSV RNA and against h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…The hybridization of cDNAs with salmon DNA was close to background level, and that with E. coli was considered negative. These results demonstrate that, like unique sequences of RSV, acute leukemia viruses, and other RNA tumor viruses (15,16,20,42,48,50), cellular sequences related tofps, yes, and ros are present in a wide variety of vertebrates, and the degree of homology correlates with the phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The hybridization of cDNAs with salmon DNA was close to background level, and that with E. coli was considered negative. These results demonstrate that, like unique sequences of RSV, acute leukemia viruses, and other RNA tumor viruses (15,16,20,42,48,50), cellular sequences related tofps, yes, and ros are present in a wide variety of vertebrates, and the degree of homology correlates with the phylogenetic relationship.…”
Section: Resultsmentioning
confidence: 73%
“…a Total cellular RNA was extracted from uninfected CEF or quail embryo fibroblasts (QEF) and from ASV-transformed CEF. 3H-labeled cDNA0nc probes (500 cpm) were incubated with various amounts (0.06 to 100 ,ug) of each RNA in 8 to 16 ,ul for 100 h under the same conditions described in the legend to Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…For preparation of feeder layers or conditioned medium, NFS/N bone marrow cell suspen- 6 sions (10 nucleated cells/ml) were plated in 60-mm tissue culture plates in RPMI 1640 medium supplemented with 20% horse serum (Flow Laboratories, Rockville, MD) and 5 × 10 -5 ME. Nonadherent cells and medium were removed after 5 d, and medium containing 15% fetal calf serum was used thereafter.…”
Section: Establishment Of Balb-msv-and Harvey-msv-transformed Hematopmentioning
confidence: 99%
“…We suspect that the fate of transfected retroviral DNA molecules differs from the fate of viral DNA molecules synthesized within a cell after retrovirus infection. Other investigators have shown that nonproducer transformed cells derived by sarcoma virus infection can have as few as one copy of proviral DNA per haploid genome (8).…”
Section: Resultsmentioning
confidence: 99%